(untitled) (Eurasian Journal of Philology Science and Education, 2024)
This article discusses the issues of high-quality sound of foreign animated films and their stylistic features of sound in the Kazakh language. The article is aimed at drawing attention to the modern picture of animated films aimed at children and adolescents, stylistic errors and shortcomings made in the translation of these cartoons, and ways to implement the executive role of the language function at the proper level. The article also assesses the specifics of the dubbing sphere and the quality in Kazakh dubbings. The issues of using the translation language and its impact on the audience depending on the age of the audience are considered. The article analyzes the stylistic features of the animated cartoons “Ralph Breaks the Internet” (2018), “Frozen 2” (2019) by the film company “Pixar”, “Luka” (2021) released by the Disney studio, dubbed into the Kazakh language, and considers the effective use of emotionally expressive shade during the translation process. The article examines the forms of motivated and unmotivated deviations of linguistic units in accordance with the plot, the use of dialect and slang words. Phrases found in the hero’s language were given as examples in three different versions: the original - English, Russian, Kazakh. Analyzing the national cognitive and linguocultural vocabulary of the hero’s language, pragmastylistic features are differentiated. Stylistics, Translation Studies, Dialectology, advanced studies of Art History, and the Law of the Republic of Kazakhstan “On Cinematography” were taken as the main theoretical literary base of the article. Key words: cinematography, dubbing, translation, stylistics, stereotype, dialect, knowledge, linguistic culture.